Growth Performance of Kasila Broiler Parent Stock Reared on Quantitative Feed Restriction under Bangladesh Condition - Hossain, M.E.; Chowdhury, S.D.; Ahammed, M.; Pramanik, M.A.H.; Rahman, M.R. (International Journal of Poultry Science, 2005)
A total of 201 Kasila broiler parent chicks were reared in an open-sided house from one-day to 22 weeks of age and growth performance and uniformity were monitored. The birds were maintained on quantitative feed restriction and their adaptability was evaluated. The experimental period was divided into three phases, phase I (day-old to 2 weeks), phase II (3 to 8 weeks) and phase III (9 to 22 weeks). The birds were provided with identical care and management like feeding, watering, ventilation, lighting, vaccination and disease control programme. Female chicks followed standard growth and feed consumption curves very closely while, male followed standard growth curve irregularly. The body weight of females at the end of 2nd, 8th and 22nd weeks were slightly higher but close to the standard while, males were little higher at 2nd & 22nd week but little lower at 8th week. Body weight gain of both females and males were lower during 3 to 8 weeks and higher during 9 to 22 weeks of age. Kasila females exhibited acceptable uniformity ranges during the study period except at 20th week. But the males showed lower trends in uniformity in most of the growth period. The birds were more prone to Mycoplasmosis during the growing period in spite of adopting preventive measures including medication. Kasila broiler parents are adaptable under Bangladesh condition if environmental stress could be minimized by taking appropriate measures and following breeder`s instructions.